(untitled) (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2020)
The article reveals the issue of the constitutional and legal status, rights and freedoms of the disabled people and the guarantees of its implementation in Ukrainian society. The author focus attention on the fact, that disability is surrounded by myths concerning the lifestyle and specific needs of people with disabilities. The process of public consciousness changing is a long and hard-working way, involving the legal basis, which regulates the constitutional and legal status of the disabled. The author states for the lack of unified terminology in Ukrainian legislative and regulatory acts, and shows the gaps and collisions in laws and relevant documents. The author concludes, that the major task of law making is setting up the law approving legal status of persons with disabilities. Whereas only this condition would make possible developing further normative-legal acts accordingly to the peculiarities and life conditions of disabled categories of people and to the actual possibilities of socio-economic conditions of our state.